Un oasis en medio de la urbe (2017)
"Due to the growth of the city of Bogota throughout the years, the public space inside some localities ended up being the resultant area of the rapid urbanization of the savanna. In the search for increasing the productivity and favoring the industrial growth, the city forgot the importance of the green spaces and gave priority to the construction of a street network and city blocks that were supported the industrialization, as happened in the locality of Antonio Nariño, where, nowadays, there are only 3,2 m2 of public space per person, whereas the WHO recommends a minimum from 10 to 15 m2. Therefore, the project seeks to re-promote and rearticulate the green spaces found in the area of direct influence of the Rio Fucha, and link them to the existing ecological structure. By achieving this there will be a new natural circuit that recovers the quality of the air and of the water of the surroundings of the river".-- Tomado del Formato de Documento de Grado.